Towards a Christian ethic of work in South Africa - Kretzschmar, L. (Faculty of Theology, University of the Free State, 2012)
This paper draws on the academic field of Christian ethics and focuses attention on an ethic of work within the South African context. Key terms such as ‘an ethic of work’, ‘a work ethic’ and ‘ethics at work’ are discussed in relation to varied experiences of work. The issues of why one ought to work and what constitutes ‘good’ work are discussed with reference to current ethical and economic challenges. I argue that a Christian worldview, or understanding of reality, provides a much more credible contribution to an ethic of work than either a materialist view of reality or a system of patronage. Recently I read a historical novel set in Wessex – what is today southern England. This was part of the Saxon kingdom of Alfred the Great in the 9th century. It was a time of war, brutal violence and suffering. Contrary to the violent culture and religion of the Danes, Alfred saw it as his calling, his work, to create a land in which justice, peace and prosperity were central features. In the historical note at the end of the book, Cornwell (2011:334) wrote this of Alfred: He was, by any measure, a most intelligent man, and he was also a good man. ... Alfred wanted a kingdom where the people of each market town would want to defend their property and their king because their prosperity was the state’s prosperity. He made a nation to which people felt they belonged because the law was fair, because effort was rewarded and because government was not tyrannical. It is not a bad prescription. Alfred’s Christian faith had an impact on his attitude to his people and the way in which he acted. Given the difficulties Wessex continued to face and the striking differences between that context and ours, what struck me about this passage was that this ruler combined intelligence with goodness and that he did not separate his prosperity from that of his people. His rule was legitimate because justice and effort rather than corruption and entitlement were rewarded. What is it that most people, whether in 9th century Wessex, or 21st century South Africa want for themselves, their families and their country? Is it not to be defended from corruption, injustice, incompetence, violence and policies that threaten the future of their country? Did not they hope for work, homes, food, health and education for their children? Did not they (and do not we) want to live without fear and with a sense of hope and purpose? My aim in this paper is to discuss the links between a Christian ethic of work and the challenges of the South African workplace. Within this context, where some are employed, even over-employed, and many more are unemployed or under-employed, this is a vital theme. In particular, different experiences of work, the issues of why one ought to work and what constitutes “good” work are discussed. Several biblical texts relevant to the various dimensions of an ethic of work are noted to highlight the importance of this theme, although space does not permit a detailed discussion of the literary and social contexts of these scriptural passages. In what follows, definitions are provided of Christian ethics, an ethic of work, employment and the context of work. Thereafter, varied work experiences and the issues of why and how one ought to work are examined with reference to the particular economic, social and environmental challenges facing South Africa. In this latter section, I contrast a Christian ethic of work with a materialist world view in which “growth” and “need” are often confused. A materialist view of reality is one which elevates the importance of material things such as money, possessions and status, above that of people and of peoplecentred values such as love of neighbour, the wellbeing of the whole community, and concern for the poor. When material considerations enjoy priority such values will be undermined, and a materialist economy will inevitably be an unjust one (Economic Justice in South Africa: A Pastoral Statement, 75). Nürnberger (2011:61-64) speaks of the distortions of “acquisitiveness and irresponsibility”, huge budget deficits, the commodification of all of life, easy credit, corruption and crime. A Christian ethic is also compared to the system of abusive patronage now common in many African countries. Patronage (or clientism) can be defined as a an extreme, unethical version of group loyalty and the unethical promotion of one’s family, ethnic group or political supporters at the expense of other members of the population (De Sardan 1999; Guest 2004:110; Kretzschmar 2008:89). Hence, patronage leads to the abuse of power and the looting of public resources. In the final section of the article, I consider when work is “good”.
Keywords: Ethics; Work; Calling; South Africa